Strategi Ketahanan Pangan di Daerah Prioritas: Studi Kasus Kecamatan Panawangan, Kabupaten Ciamis - Lidya Nur Amalia; Muthiah Syakirotin; Perdi Setiawan; Siti Nur Anisah; Yoga Gandara; Nazril Hasbilah; Susi Amelia Putri (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Food security is a strategic issue in regional development, particularly in agrarian areas such as Ciamis Regency, which faces challenges such as declining food production, land conversion, distribution inefficiencies, and increasing food needs due to population growth. This study aims to analyze strategies for improving local-based food security in Panawangan District, specifically in Girilaya and Kertayasa Villages, through a multidimensional approach encompassing aspects of food availability, accessibility, distribution, and utilization. The study used a mixed method with primary data collection through household surveys and in-depth interviews, as well as secondary data from relevant government agencies. A total of 60 respondents were selected using a random sampling technique. Priority strategies were determined through Focus Group Discussions (FGDs) with stakeholders, then analyzed using the Multi Criteria Decision Analysis (MCDA) method with the PROMETHEE approach. The results of the analysis indicate that the strategy of providing incentives to local farmers and traders (Type III) is the most optimal alternative in improving regional food security because it has the highest contribution to increasing income, actor acceptance, and logistics efficiency. Sensitivity analysis shows that this strategy remains superior across most weighting criteria changes, while regulatory strategies and strengthening healthy food consumption programs demonstrate high levels of long-term policy stability. The study's findings confirm that a combination of regulatory-based strategies, economic incentives, and strengthening local food institutions is the most effective and sustainable approach to strengthening food sovereignty in Ciamis Regency.